2012
DOI: 10.1080/02673037.2012.632620
|View full text |Cite
|
Sign up to set email alerts
|

Place Attachment in Deprived Neighbourhoods: The Impacts of Population Turnover and Social Mix

Abstract: This paper examines the determinants of individual place attachment, focussing in particular on differences between deprived and others neighbourhoods, and on the impacts of population turnover and social mix. It uses a multi-level modelling approach to take account of both individual-and neighbourhood-level determinants. Data are drawn from a large sample government survey, the Citizenship Survey 2005, to which a variety of neighbourhood-level data have been attached. The paper argues that attachment is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
6
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(158 citation statements)
references
References 36 publications
8
132
6
12
Order By: Relevance
“…A weak sense of community in regeneration areas as a result of residential instability (Bailey et al, 2012) also provides an opportunity for migrant groups, with some help from other local people, to make a contribution over time, through developing self-support and new community structures where these were absent and contributing to existing community groups in ways that develop more positive feelings about place, as found in other UK studies (Bowes, Ferguson, & Sim, 2009; Sim & Bowes, 2007; Stewart & Shaffer, 2005). In addition, regeneration areas received additional state funding and services to support the social integration and safety of migrants, and these are likely to benefit all residents (FMR Research, 2003; ODS Consulting, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A weak sense of community in regeneration areas as a result of residential instability (Bailey et al, 2012) also provides an opportunity for migrant groups, with some help from other local people, to make a contribution over time, through developing self-support and new community structures where these were absent and contributing to existing community groups in ways that develop more positive feelings about place, as found in other UK studies (Bowes, Ferguson, & Sim, 2009; Sim & Bowes, 2007; Stewart & Shaffer, 2005). In addition, regeneration areas received additional state funding and services to support the social integration and safety of migrants, and these are likely to benefit all residents (FMR Research, 2003; ODS Consulting, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other UK research has shown that place attachment falls for White residents at higher levels of (objectively measured) ethnic diversity (Bailey, Kearns, & Livingston, 2012) and, thus, for community cohesion outcomes we examined associations of perceived diversity with belonging, social engagement, and trust. For belonging, respondents were asked how much they felt that they belonged to the neighborhood and how much they felt part of the community.…”
Section: Methodsmentioning
confidence: 99%
“…The parents came together through their acts of adaptation of the programme, such as the smoking breaks in the playground and cooking in the school kitchen rather than at home, which became acts of reclaiming the place and imbuing it with new meanings. The place became one to which individuals could form an attachment or 'locational ties' (Tönnies 2002), making new meanings and associations with the place and building local social networks (Bailey et al 2012) and becoming a 'community of place ' (Tönnies 2001, p.27). …”
Section: Discussionmentioning
confidence: 99%
“…The parents came together through their acts of adaptation of the programme, such as the smoking breaks in the playground and cooking in the school kitchen rather than at home, which became acts of reclaiming the place and imbuing it with new meanings. The place became one to which individuals could form an attachment or 'locational ties' (Tönnies 2002), making new meanings and associations with the place and building local social networks (Bailey et al 2012) and becoming a 'community of place ' (Tönnies 2001, p.27).The timing of the programme, outside the school day, and the new configuration of the place as a meeting and eating place for families led to one interviewee describing it as taking on the role of a 'safety net' for some individuals as they realised they could have a voice in a space that had previously been thought of as bounded by hierarchical relationships in school (teachers) and out of school (parents). In such a way the programme and the deviation from its structures allowed for locational and relational ties to be created where new roles were negotiated and new kinds of relationship were formed.…”
mentioning
confidence: 99%
“…This can be conceptualised as a series of submarket curves, each having different intercepts for each submarket but being similar in slope due to the same micro-level drivers having the same effects on the transaction process across all submarkets. However, it is possible that the effect of any micro-level covariate that determines cap rates will vary between submarkets, and Bailey et al (2012) highlight the benefit of the hierarchical approach in that it allows for the existence of more complex patterns of variance to be investigated. This can be achieved by specifying an additional macro-level equation as:…”
Section: Operationalising the Model Previous Studiesmentioning
confidence: 99%